Therapeutic Effect of Core Stability Training Combined with Extracorporeal Shock Wave on Lumbar Disc Herniation - Shuo LI; Lishuang LIU; Jinna ZHOU; Qiaoyun XIANG; Tingting LUAN; Wenwen WANG (康复学报)
Objective:To investigate the effects of core stability training combined with extracorporeal shock wave on patients with lumbar disc herniation.Methods:A total of 90 patients with lumbar disc herniation treated in Beijing Rehabilitation Hospital affiliated to Capital Medical University were randomly assigned to the Core stability training group, the Extracorporeal shock wave group and the Combined group, with 30 cases in each group. The Extracorporeal shock wave group was given extracorporeal shock wave treatment with parameters of voltage 6 kV, frequency of 10 to 15 MHz, pressure of 1.5 to 2.5 bar, 2 000 times of impact, energy intensity of 0.16 mJ/mm2, 2 times per week, 3 consecutive months. The Core stability training group received core stability training. SPS-F11 multi-point multi-axis suspension rehabilitation training system was applied, under the guidance of the same rehabilitation doctor. Following the principle of gradual progression, the training time and frequency were slowly increased, from easy to difficult, from simple to complex, including supine position, lateral position and prone position training, 40 minutes each time, 5 times a week, continuous treatment for 3 months. The Combined group was given core stability training and extracorporeal shock wave therapy, and the method was the same as above. The pain degree was evaluated by visual analogue score (VAS) before treatment, 3 months of treatment and 6 months after treatment. The lumbar spine function was evaluated by Oswestry dysfunction index (ODI). SF-36 quality of life scale (SF-36) was used to evaluate the overall health status of the patients. The effective rate was calculated at 3 months of the treatment. The adverse reactions were recorded and all the patients were followed up for one year after the treatment. The recurrence of the three groups was observed.Results:There was no significant difference in VAS, ODI and SF-36 scores among the three groups before the treatment (P> 0.05). At 3 months of treatment and 6 months after treatment, the VAS score and ODI score in the three groups were lower than those before the treatment (P< 0.05), the SF-36 score were higher than those before the treatment (P< 0.05), and the changes of VAS score and ODI score in the Combined group were most obvious compared with the Core stability training group and the Extracorporeal shock wave group (P< 0.05). After 3 months of treatment, the effective rate in the Combined group was higher than that in the Core stability training group (P< 0.05), and the effective rate in the two groups was higher respectively than that in the Extracorporeal shock wave group (P< 0.05). One year after the treatment, the recurrence rate in the Combined group was significantly lower than that in the Core stability training group and the Extracorporeal shock wave group (P< 0.05). No serious adverse reactions occurred in the three groups during the treatment.Conclusion:Core stability training combined with extracorporeal shock wave treatment has the better effect on lumbar disc herniation, and can enhance lumbar function and relieve lumbar pain, which is safe and not easy to relapse.